Benign Fibrous Histiocytoma of the Buccal Mucosa: Case Report and Literature Review. (14th June 2010) - Giovani, Paraskevi; Patrikidou, Anna; Ntomouchtsis, Aris; Meditskou, Soultana; Thuau, Henri; Vahtsevanos, Kostas
Abstract : Benign fibrous histiocytoma is an interesting and challenging entity even in its most usual, cutaneous presentation. Noncutaneous presentation is extremely limited, even more so for the mucosa of the head and neck area. We herein report such a case, describing the clinical characteristics of the lesion, complete diagnostic evaluation, management, and follow-up. Diagnostic histopathological challenges are specifically illustrated. A complete review of the relevant literature is also included.